Implementatiton Of Dzikir Therapy On Elderly People Experiencing Anxiety Due To Diabetes Mellitus In The Sindangkasih Community Health Center Area, Ciamis Regency - Rizky Fauzan Rachman; Peni Cahyati; Iwan Somantri; Asep Riyana (Lembaga Pengembangan Kinerja Dosen, 2025)
Based on data collected from the Sindangkasih Health Center UPTD, in 2024 there were 601 recorded cases of diabetes mellitus. By 2025, the number of visits by diabetes mellitus patients fluctuated each month. In January, there were 8 male and 26 female patient visits, while in February there were 9 male and 26 female visits. This study aims to describe the reduction of anxiety symptoms among elderly individuals suffering from diabetes mellitus. Type II diabetes mellitus (Type II DM) represents the most prevalent form of diabetes, comprising approximately 85–90% of all cases worldwide. This condition is commonly observed in older adults and poses a major global health challenge. The elderly, defined as individuals aged 60 years and above, often experience anxiety related to their health conditions. Anxiety itself is an unpleasant emotional state characterized by feelings of worry, fear, and unease at varying intensities. Dhikr, or the remembrance of Allah, serves as a spiritual practice to achieve calmness and closeness to God. This research employs a qualitative descriptive method with a case study approach to explore nursing issues and intervention strategies. The applied intervention—dhikr therapy—was used to help elderly patients reduce anxiety symptom scores. A five-day evaluation revealed that both Patient 1 and Patient 2 showed improvement, each exhibiting a reduction of 10 anxiety-related symptoms. The findings indicate that dhikr therapy effectively lowers anxiety levels and enhances patients’ ability to manage their emotional well-being.